A method for preparing bipolar conjugated carbonyl compounds and application thereof

Through the polymerization reaction of tetraamic phthalocyanine compounds and bianhydride compounds, a bipolar conjugated carbonyl polymer organic electrode material was prepared, which solved the problems of environmental pollution and unipolar properties of traditional battery materials, and achieved bipolar electrochemical properties with high energy density and power density.

CN116284774BActive Publication Date: 2025-03-18SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310271549.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-20
Publication Date
2025-03-18
Estimated Expiration
2043-03-20

AI Technical Summary

Technical Problem

The electrode materials of existing lithium-ion batteries have environmental problems such as heavy metal pollution, water pollution and soil pollution, and traditional organic compounds can only be used as monopole materials, which is difficult to meet the needs of bipolar electrochemical properties.

Method used

By polymerizing tetraamic phthalocyanine compounds with bianhydride compounds, a bipolar conjugated carbonyl polymer organic electrode material is prepared. This material can be used as both a positive electrode and an negative electrode, and has good flexibility and electrochemical properties.

Benefits of technology

The preparation of bipolar electrode materials has been realized, with stable working voltage, high energy density and power density, and simple process and low cost, with good development prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116284774B_ABST
    Figure CN116284774B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a bipolar conjugated carbonyl compound and its application. The method comprises the following steps: mixing a tetraaminophthalocyanine compound, a dianhydride compound and a solvent, and then adding a catalyst to react to obtain the bipolar conjugated carbonyl compound. The present invention synthesizes a bipolar conjugated carbonyl polymer organic electrode material, which can be used as a positive electrode and a negative electrode at the same time, and the assembled organic symmetric lithium ion battery exhibits excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of organic electrode materials, and in particular relates to a method for preparing a bipolar conjugated carbonyl compound and an application thereof. Background Art

[0002] At present, the extensive use of fossil fuels such as oil and coal has caused the depletion of fossil energy, serious environmental pollution and global warming. Therefore, it is particularly urgent to develop renewable clean energy to replace traditional fossil energy and seek harmonious development between people and the environment. However, renewable energy, especially new energy such as wind power and solar energy, has the disadvantages of strong timeliness, regionality and inability to be directly stored. In summary, the development of green energy storage devices with both high power density and high energy density is one of the effective means to solve the above problems.

[0003] At present, due to environmental problems such as heavy metal pollution, water pollution and soil pollution, people are worried about the future application prospects of lithium-ion batteries. Therefore, the development and preparation of high-performance, sustainable and environmentally friendly electrode materials are crucial for the further application of lithium-ion batteries. The electrode materials used in lithium-ion organic battery systems are mainly derived from organic compounds composed of light elements (such as C, H, O, N and S, etc.), which have the advantages of high specific capacity, low cost, low environmental pollution and abundant resources. Most importantly, organic compounds have good molecular designability, which can not only achieve high specific capacity through structural design, but also achieve cyclic stability through polymerization reaction, and enhance electronic conductivity at the molecular level by extending the conjugated system.

[0004] In recent years, most traditional organic compounds can only be used as positive or negative electrode materials for lithium-ion batteries, while phthalocyanine compounds have bipolar properties, which enable them to both accept and provide electrons. During the electrochemical reaction, the 18π electron structure in phthalocyanine compounds can be oxidized to a 16π electron structure, or reduced to a 20π electron structure. In addition, the stable CN bond in its structure can provide a higher reversible capacity.

[0005] Therefore, in the art, it is desired to develop a bipolar organic electrode material, and the symmetrical polymer full battery prepared therefrom has stable operating voltage, high energy density and power density. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a bipolar conjugated carbonyl compound and its application. The present invention synthesizes a bipolar conjugated carbonyl polymer organic electrode material, which can be used as both a positive electrode and a negative electrode, and the assembled organic symmetric lithium ion battery exhibits excellent electrochemical performance.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a bipolar conjugated carbonyl compound, the method comprising the following steps:

[0009] The tetraaminophthalocyanine compound, the dianhydride compound and the solvent are mixed, and then a catalyst is added to react to obtain the bipolar conjugated carbonyl compound.

[0010] The present invention utilizes tetraaminophthalocyanine compounds and dianhydride compounds to undergo polymerization reaction to prepare a bipolar conjugated carbonyl polymer organic electrode material, which can be used as both a positive electrode and a negative electrode and has good flexibility. Compared with other battery systems, it not only has the advantages of simple manufacturing process and low cost, but also has the advantages of matching reaction kinetics of positive and negative electrode materials and consistent electrolyte compatibility, so it has good development prospects.

[0011] Preferably, the functionality of the amino group in the tetraaminophthalocyanine compound is 4.

[0012] Preferably, the tetraaminophthalocyanine compound includes any one of tetraaminocopper phthalocyanine, tetraaminoiron phthalocyanine, tetraaminocobalt phthalocyanine or tetraaminonickel phthalocyanine, or a combination of at least two thereof.

[0013] Preferably, the functionality of the anhydride group in the dianhydride compound is 2.

[0014] Preferably, the dianhydride compound includes any one of naphthalenetetracarboxylic dianhydride, pyromellitic dianhydride or pyrenetetracarboxylic dianhydride, or a combination of at least two thereof.

[0015] Preferably, the molar ratio of the tetraaminophthalocyanine compound to the dianhydride compound is (1-1.5):(2-3), for example, 1:2, 1:3, 1.5:2, 1.5:2.5, 1.5:3, etc.

[0016] In the present invention, the molar ratio of the tetraaminophthalocyanine compound to the dianhydride compound is controlled within a suitable range. A too low molar ratio will result in insufficient reaction of the phthalocyanine, whereas a too high molar ratio will result in insufficient reaction of the dianhydride compound.

[0017] Preferably, the solvent includes any one of N,N-dimethylacetamide, N,N-dimethylformamide or N-methylpyrrolidone, or a combination of at least two thereof.

[0018] Preferably, the catalyst comprises aqueous acetic acid.

[0019] Preferably, the concentration of the catalyst is 5-8 mol / L, for example, 5 mol / L, 5.5 mol / L, 6 mol / L, 6.5 mol / L, 7 mol / L, 7.5 mol / L, 8 mol / L, etc.

[0020] Preferably, the reaction is carried out under an inert atmosphere.

[0021] Preferably, the inert atmosphere comprises nitrogen and / or argon.

[0022] Preferably, the reaction temperature is 120-160°C, for example, 120°C, 130°C, 140°C, 150°C, 160°C, etc.; the reaction time is 3-6 days, for example, 3 days, 4 days, 5 days, 6 days, etc.

[0023] Preferably, the reaction further includes post-treatment and purification steps.

[0024] Preferably, the post-treatment includes centrifugation and washing.

[0025] Preferably, the washing treatment uses N,N-dimethylformamide, tetrahydrofuran and acetone in sequence.

[0026] Preferably, the purification is carried out by Soxhlet extraction.

[0027] In a second aspect, the present invention provides a bipolar conjugated carbonyl compound, wherein the bipolar conjugated carbonyl compound is prepared by the method for preparing a bipolar conjugated carbonyl compound according to the first aspect.

[0028] In a third aspect, the present invention provides a bipolar electrode material, wherein the bipolar electrode material is the bipolar conjugated carbonyl compound according to the second aspect.

[0029] In a fourth aspect, the present invention provides a secondary battery, comprising an electrode sheet, an electrolyte and a separator, wherein the electrode sheet comprises the bipolar electrode material according to the third aspect.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] The present invention provides a method for preparing a bipolar conjugated carbonyl compound, which utilizes a tetraaminophthalocyanine compound and a dianhydride compound to undergo polymerization reaction to prepare a bipolar conjugated carbonyl polymer organic electrode material, which can be used as both a positive electrode and a negative electrode and has good flexibility. Compared with other battery systems, it not only has the advantages of simple manufacturing process and low cost, but also has the advantages of matching reaction kinetics of positive and negative electrode materials and consistent electrolyte compatibility, so it has good development prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The synthetic route of the bipolar conjugated carbonyl compound provided in Example 1;

[0033] Figure 2 This is a structural characterization diagram of the bipolar conjugated carbonyl compound provided in Example 1. DETAILED DESCRIPTION

[0034] The technical solution of the present invention is further described below by combining the accompanying drawings and specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0035] Example 1

[0036] This embodiment provides a method for preparing a bipolar conjugated carbonyl compound, such as Figure 1 As shown, the method comprises the following steps:

[0037] 44.9 mg, 0.07 mmol of tetraamino copper phthalocyanine (CuTAPc) and 36.8 mg, 0.14 mmol of naphthalenetetracarboxylic dianhydride (NTCDA) were dissolved in 1.2 mL of N, N-dimethylacetamide solution, and then 60 μL of 6 mol / L acetic acid aqueous solution was added as a catalyst. The above solution was placed in a reaction tube, and after three freeze-vacuum-thaw cycles, the reaction tube was heat-sealed so that the system was in a nitrogen atmosphere and placed in a 150°C oven for reaction for 5 days. Finally, the product was collected by centrifugation and repeatedly washed with N, N-dimethylformamide, tetrahydrofuran and acetone until the eluate was colorless. Then, tetrahydrofuran was further used as a solvent, and it was purified in a Soxhlet extractor, and the bipolar conjugated carbonyl compound was obtained after vacuum drying at 65°C.

[0038] Figure 2 This is a structural characterization diagram of the bipolar conjugated carbonyl compound provided in Example 1. After polymerization, the infrared spectrum of the polymer is at 1711 cm -1 The stretching vibration peak of -C=O bond appears at 1675cm -1 The stretching vibration peak at 1610 cm -1 The newly emerged stretching vibration peaks indicate the existence of -CN bonds in the polymer, while the disappeared amino and -COC characteristic peaks prove the successful Schiff base reaction between tetraaminocopper phthalocyanine and naphthalenetetracarboxylic dianhydride.

[0039] Example 2

[0040] This embodiment provides a method for preparing a bipolar conjugated carbonyl compound, the method comprising the following steps:

[0041] 44.9 mg, 0.07 mmol of tetraamino copper phthalocyanine (CuTAPc) and 36.8 mg, 0.14 mmol of naphthalenetetracarboxylic dianhydride (NTCDA) were dissolved in 1.2 mL of N, N-dimethylacetamide solution, and then 60 μL of 6 mol / L acetic acid aqueous solution was added as a catalyst. The above solution was placed in a reaction tube, and after three freeze-vacuum-thaw cycles, the reaction tube was heat-sealed so that the system was in a nitrogen atmosphere and placed in a 120°C oven for reaction for 6 days. Finally, the product was collected by centrifugation and repeatedly washed with N, N-dimethylformamide, tetrahydrofuran and acetone until the eluate was colorless. Then, tetrahydrofuran was further used as a solvent, and it was purified in a Soxhlet extractor, and the bipolar conjugated carbonyl compound was obtained after vacuum drying at 65°C.

[0042] Example 3

[0043] This embodiment provides a method for preparing a bipolar conjugated carbonyl compound, the method comprising the following steps:

[0044] 44.9 mg, 0.07 mmol of tetraamino copper phthalocyanine (CuTAPc) and 36.8 mg, 0.14 mmol of naphthalenetetracarboxylic dianhydride (NTCDA) were dissolved in 1.2 mL of N, N-dimethylacetamide solution, and then 60 μL of 6 mol / L acetic acid aqueous solution was added as a catalyst. The above solution was placed in a reaction tube, and after three freeze-vacuum-thaw cycles, the reaction tube was heat-sealed so that the system was in a nitrogen atmosphere and placed in a 160°C oven for reaction for 3 days. Finally, the product was collected by centrifugation and repeatedly washed with N, N-dimethylformamide, tetrahydrofuran and acetone until the eluate was colorless. Then, tetrahydrofuran was further used as a solvent, and it was purified in a Soxhlet extractor, and the bipolar conjugated carbonyl compound was obtained after vacuum drying at 65°C.

[0045] Example 4

[0046] The difference between this embodiment and embodiment 1 is that the molar ratio of tetraaminocopper phthalocyanine to naphthalenetetracarboxylic dianhydride is 1:1, and the other aspects are the same as those of embodiment 1.

[0047] Example 5

[0048] The difference between this embodiment and embodiment 1 is that the molar ratio of tetraamino copper phthalocyanine to naphthalenetetracarboxylic dianhydride is 1:5, and the other parts are the same as those in embodiment 1. The other parts are the same as those in embodiment 1.

[0049] Example 6

[0050] The difference between this embodiment and embodiment 1 is that tetraaminocopper phthalocyanine is replaced by tetraaminoiron phthalocyanine, and the rest is the same as embodiment 1.

[0051] Example 7

[0052] The difference between this embodiment and embodiment 1 is that naphthalenetetracarboxylic dianhydride is replaced by pyrenetetracarboxylic dianhydride, and the rest is the same as embodiment 1.

[0053] Comparative Example 1

[0054] This comparative example provides a tetraaminocopper phthalocyanine material.

[0055] Comparative Example 2

[0056] This comparative example provides a naphthalenetetracarboxylic dianhydride material.

[0057] Comparative Example 3

[0058] This comparative example provides a bipolar material, and the preparation method is as follows:

[0059] 2 mmol of 2.6-diaminoanthraquinone and 2 mmol of pyromellitic anhydride were dissolved in 25 mL of N-methylpyrrolidone, and the system was placed in an argon atmosphere and placed in an oven at 180°C for reaction for 3 days. Finally, the product was collected by centrifugation and repeatedly washed with N,N-dimethylformamide, tetrahydrofuran and acetone until the eluate was colorless. Then, tetrahydrofuran was further used as a solvent and purified in a Soxhlet extractor, and the bipolar material was obtained after vacuum drying at 65°C.

[0060] Application Examples 1 to 7 and Comparative Application Examples 1 to 3

[0061] The materials prepared in Examples 1-7 and Comparative Examples 1-3 were prepared into lithium ion batteries, and the preparation method was as follows:

[0062] Preparation of positive electrode: The materials prepared in Examples 1-7 and Comparative Examples 1-3, the conductive agent (acetylene black) and the binder (polyvinylidene fluoride) were ground in a mass ratio of 4:5:1, and then N-methylpyrrolidone was added as a solvent and carefully ground for 1-2 hours. After grinding, the prepared slurry was evenly coated on a clean aluminum foil as the positive electrode of the lithium-ion battery, vacuum dried at 100°C for 12 hours, and after rolling, the electrode material was cut into 12 mm diameter discs using a circular punching machine;

[0063] Preparation of negative electrode: Grind the materials prepared in Examples 1-7 and Comparative Examples 1-3, the conductive agent (acetylene black) and the binder (polyvinylidene fluoride) in a mass ratio of 4:5:1, and then add N-methylpyrrolidone as a solvent and grind carefully for more than 1 hour. After grinding, the prepared slurry is evenly coated on a clean copper foil as the negative electrode of the lithium ion battery, vacuum dried at 100°C for 24 hours, and after rolling, the electrode material is cut into 12 mm diameter discs using a circular punching machine;

[0064] Preparation of flexible electrodes: Disperse 20 mg of the materials prepared in Examples 1-7 and Comparative Examples 1-3 and 20 mg of carbon nanotubes (CNTs) in 20 mL of anhydrous ethanol at a mass ratio of 1:1, with an ultrasonic power of 150 W. After 2 hours of ultrasonic treatment, a uniformly dispersed suspension is obtained. Mix the obtained uniformly dispersed suspension and continue ultrasonication for 1 hour. Finally, filter the above suspension by vacuum filtration. After vacuum drying at 70°C, a flexible self-supporting film is obtained. Cut the obtained flexible self-supporting film into a size of 5 cm × 8 cm as the positive and negative electrodes of an organic symmetrical flexible lithium-ion battery;

[0065] Preparation of organic symmetric flexible lithium-ion battery: The obtained flexible self-supporting film is used as the positive and negative electrodes respectively, the Celgard2400 porous polypropylene film is used as the separator, the electrolyte is a mixed solution of DOL and DME containing a concentration of 1 mol / L LiTFSI (volume ratio of 1:1), aluminum-plastic film is used as the packaging material, and nickel strips are used as the positive and negative electrode tabs to assemble into an organic symmetric flexible lithium-ion battery.

[0066] Test conditions

[0067] The positive electrode sheets, negative electrode sheets and organic symmetrical flexible lithium-ion batteries prepared in Examples 1-7 and Comparative Examples 1-3 were subjected to performance tests, and the test methods are as follows:

[0068] (1) Positive electrode test: The assembled half-cell is tested for the first discharge specific capacity and cycle test at a current density of 200 mA / g at a voltage of 1.5-4.5 V at 25°C;

[0069] (2) Negative electrode test: The assembled half-cell was tested for the first discharge specific capacity and cycle test at a current density of 50 mA / g at a voltage of 0.01-3 V at 25°C;

[0070] (3) Organic symmetric flexible lithium-ion battery test: The assembled organic symmetric flexible lithium-ion battery was tested at 25°C, a voltage of 1-4V, and the first discharge specific capacity and cycle test at a current density of 100mA / g.

[0071] The test results are shown in Table 1-Table 3:

[0072] Table 1: Comparison of performance of various examples as positive electrodes for lithium-ion batteries

[0073]

[0074] Table 2: Comparison of performance of various examples as negative electrodes for lithium-ion batteries

[0075]

[0076] Table 3: Organic symmetric lithium-ion battery performance

[0077]

[0078] It can be seen from the data in Tables 1 to 3 that the bipolar conjugated carbonyl compounds prepared in Application Examples 1 to 3 provided by the present invention, whether as positive electrode materials or negative electrode materials, or even when assembled into full batteries, have an initial discharge capacity and a discharge capacity after cycling at a relatively high level, which is superior to the comprehensive performance of the materials provided in Comparative Application Examples 1 to 3.

[0079] Compared with Application Example 1, Application Example 4 is a case where the molar ratio of tetraaminocopper phthalocyanine to naphthalenetetracarboxylic dianhydride is too low, which causes insufficient reaction of phthalocyanine, thereby reducing the electrochemical performance of the negative electrode; Application Example 5 is a case where the molar ratio of tetraaminocopper phthalocyanine to naphthalenetetracarboxylic dianhydride is too high, which causes insufficient anhydride reaction of the dianhydride compound, thereby reducing the electrochemical performance of the positive electrode.

[0080] Compared with Application Example 1, the performance of Application Examples 6 and 7 after replacing other monomers deteriorates, which is mainly because copper ions have better ionic conductivity than iron lithium ions, which can effectively improve the transmission performance of the material. After replacing naphthalenetetracarboxylic dianhydride with pyrenetetracarboxylic dianhydride, the overall theoretical specific capacity of the polymer decreases, so the performance deteriorates.

[0081] The performance of the unipolar electrode materials provided in Comparative Application Examples 1-2 is inferior to the electrochemical performance of the bipolar conjugated carbonyl compound provided by the present invention; the bipolar material provided in Comparative Application Example 3 also cannot achieve the technical effect of the present invention.

[0082] The applicant declares that the present invention illustrates the lithium ion battery non-aqueous electrolyte and its application through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a bipolar conjugated carbonyl compound, characterized in that: The method comprises the following steps: A tetraaminophthalocyanine compound, a dianhydride compound and a solvent are mixed, and then a catalyst is added to react to obtain the bipolar conjugated carbonyl compound; The tetraaminophthalocyanine compound is tetraaminocopper phthalocyanine; The dianhydride compound is naphthalenetetracarboxylic dianhydride and / or pyrenetetracarboxylic dianhydride; The molar ratio of the tetraaminophthalocyanine compound to the dianhydride compound is (1-1.5):(2-3); The catalyst includes an aqueous solution of acetic acid; The concentration of the catalyst is 5-8 mol / L; The reaction temperature is 120-160° C. and the reaction time is 3-6 days.

2. The method according to claim 1, characterized in that The solvent includes any one of N,N-dimethylacetamide, N,N-dimethylformamide or N-methylpyrrolidone or a combination of at least two thereof.

3. The method according to claim 1, characterized in that The reaction was carried out under an inert atmosphere.

4. The method according to claim 3, characterized in that The inert atmosphere includes nitrogen and / or argon.

5. The method according to claim 1, characterized in that The reaction also includes post-treatment and purification steps.

6. The method according to claim 5, characterized in that The post-treatment includes centrifugation and washing.

7. The method according to claim 6, characterized in that The washing treatment uses N,N-dimethylformamide, tetrahydrofuran and acetone in sequence for washing.

8. The method according to claim 5, characterized in that The purification is carried out by Soxhlet extraction.

9. A bipolar conjugated carbonyl compound, characterized in that: The bipolar conjugated carbonyl compound is prepared by the method for preparing a bipolar conjugated carbonyl compound according to any one of claims 1 to 8.

10. A bipolar electrode material, characterized in that: The bipolar electrode material is the bipolar conjugated carbonyl compound according to claim 9.

11. A secondary battery, characterized in that: The secondary battery includes an electrode sheet, an electrolyte, and a separator, and the electrode sheet includes the bipolar electrode material according to claim 10 .